Increasing the reliability of voltage control in the formation of modern electrical networks - M. Muratov, Xakim; I. Turaev, Akramjon; M. Mahammadiev, Farrukh (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: providing reliable voltage control is a major challenge in modern power grids. Fluctuations in renewable energy sources, increasing electrification and aging infrastructure can cause voltage fluctuations. Advanced techniques such as smart grid technologies, flexible AC transmission systems, and coordinated management of distributed energy resources are being used to improve voltage regulation. Reliable voltage control is essential to ensure power quality, equipment protection, and grid stability. Regulatory frameworks and market incentives are being developed to attract investment in voltage management solutions. Ensuring reliable voltage control is critical to integrating renewable energy sources and ensuring a stable and resilient power system. Aim: applies to the critical importance of maintaining stable and reliable voltage levels in modern power systems and to address the growing challenges of voltage control as power systems evolve to include more distributed generation sources and new electrified loads, or with a focus on techniques and strategies. Methods: regression analysis, comparison method, mathematical statistics, modeling and modern data processing methods were used to improve stress control. Results: this is explained by the modeling of distributed generation sources and power grids based on data obtained using modern programs, results and their compatibility, as well as the correspondence of theoretical and experimental results.